2006
DOI: 10.1007/s10641-006-9106-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of bomb radiocarbon chronologies to shortfin mako (Isurus oxyrinchus) age validation

Abstract: Age estimation is an issue for the shortfin mako, Isurus oxyrinchus, because of disagreement on vertebral band-pair deposition periodicity. In the 1950s-1960s, thermonuclear testing released large amounts of radiocarbon into the atmosphere, which diffused into the ocean through gas exchange. This influx created a time-specific marker that can be used in age validation. Annual band-pair deposition in the porbeagle, Lamna nasus, was validated in a previous study and indicated preliminary annual deposition in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…For Atlantic shortfin mako, the annual formation of one growth band pair was validated by bomb radiocarbon experiment (Campana et al 2002;Ardizzone et al 2006) and by OTC-injection experiment , therefore, we revised the growth curves reported by Pratt and Casey (1983) to reflect annual, instead of biannual, band pair deposition. The revised curves yielded a faster growth rate for both sexes than are suggested by our data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Atlantic shortfin mako, the annual formation of one growth band pair was validated by bomb radiocarbon experiment (Campana et al 2002;Ardizzone et al 2006) and by OTC-injection experiment , therefore, we revised the growth curves reported by Pratt and Casey (1983) to reflect annual, instead of biannual, band pair deposition. The revised curves yielded a faster growth rate for both sexes than are suggested by our data.…”
Section: Resultsmentioning
confidence: 99%
“…However, this conflict has been settled by recent studies using bomb radiocarbon and tetracycline injection in individuals from the Atlantic Ocean (Campana et al 2002;Natanson et al 2006;Ardizzone et al 2006). These results confirmed that one growth band pair is formed annually in individuals from both the Pacific and the Atlantic oceans.…”
Section: Introductionmentioning
confidence: 86%
“…While this exciting new validation approach is quite promising, it is also highly technical and expensive, thus no new papers have been published to date. However, three papers were presented at this symposium, which appear in these proceedings (see Ardizzone et al 2006;Campana et al 2006;Kerr et al 2006) In our review of the recent literature (Cailliet and Goldman 2004), including the more recent 28 studies, validation studies have not been very common for chondrichthyan fishes. This is mainly because of their limited accessibility, large size and mobility, and the difficulty of obtaining monthly, or even seasonal, samples.…”
Section: Validation Analysismentioning
confidence: 99%
“…A qualitative comparison of the white shark D 14 C record was made with existing marine records including two otolith-based records, the yelloweye rockfish, Sebastes ruberrimus, (Kerr et al 2004) and Pacific halibut, Hypoglossus stenolepis, (Piner and Wischniowski 2004), and three vertebra-based shark records, the western North Atlantic porbeagle (Campana et al 2002), western North Atlantic shortfin mako (Campana et al 2002;Ardizzone et al 2006), and the western South Pacific school shark (Kalish and Johnston 2001).…”
Section: Radiocarbon Analysismentioning
confidence: 99%